Mapping of Youth Theatre workshops/organisations in Cyprus - Polyviou, Eleni (Education & Theatre, 2022)
This article describes the main findings of a primary research which was conducted in Cyprus during 2019–2020 and is part of the doctoral dissertation of the author. The purpose of the research was to outline the overall picture of the organisations that were active in Cyprus in the field of Youth Theatre during the years 2017–2020 so that its results could be integrated into the general geographical context that the dissertation examines. The research records the objectives of Youth Theatre programmes, the composition of organisations and the theatre activities that are carried out. In addition, it examines whether these programmes result in the staging of a theatrical performance and to what extent teenagers participate in the various aspects of the process. As a methodological tool, a specially designed questionnaire was used.